Postcard from Marianne and Viktor Homburger to Max Bredig, August 7, 1937 - Homburger, Marianne; Homburger, Viktor (1937)
The Homburger family writes to Max Bredig (1902-1977) with updates from Karlsruhe, Germany. Viktor Homburger (1888-1968) tells Max that he is forwarding him a newsletter. Marianne Homburger (1903-1987) shares health news about their father, Georg Bredig (1868-1944).
Keywords: Homburger, Viktor, 1888-1968; Bredig, Max Albert, 1902-1977; Homburger, Marianne, 1903-1986